Escolas indígenas diferenciadas no Brasil, interculturalidade e (des)colonialidade: Um estudo a partir de teses e dissertações - Rocha, Marina da (Universidade do Vale do Rio dos Sinos, 2013)
This present study aims to identify and carry out a reflection on movements of differentiated indigenous schools in Brazil, from the context of tensioning between functional and critical interculturality, in relation to (dis) coloniality.. The research focused on the bibliographic review, specifically of theses and dissertations, selected from the Thesis and Dissertations Catalog - CAPES and the Brazilian Digital Library of Theses and Dissertations – BDTD, produced in Brazil, which addressed the theme of differentiated indigenous school education and are related to interculturality. The selection of sources as well as their interpretation was developed based on two theoretical categories. Because they are differentiated schools, as the name indicates, one can not speak of the construction of an indigenous school in a generic way, but rather of differentiated indigenous schools, in the plural, taking into account their diversities. From each experience the study highlights advances or limits, as to the perspective of a critical interculturality from a decolonial look. Thus, it has been identified that there are schools that are constructed based on the demands of the indigenous communities themselves. However, there are still impositions, with visible signs of the coloniality present in many spaces in which these schools are inserted. Among the study's findings highlight that these educational institutions have contradictory characteristics of decoloniality and critical intercultural amid coloniality reproduction signals in the context of functional interculturalism.
Keywords: Educação Indígena; Escola indígena diferenciada; Interculturalidade; (Des)colonialidade; Indigenous education; Differentiated indigenous school; Interculturality; (De)coloniality.; ACCNPQ::Ciências Humanas::Educação